PENERAPAN LITERASI DIGITAL MELALUI LSM PADA TINGKAT SEKOLAH DASAR (Studi Kasus SD Masehi Kota Pekalongan) - Mutiara Karima; Rochman Hadi Mustofa (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aimed to describe the application of digital literacy at the elementary school level during online learning. This research used a qualitative approach with a case study design at Masehi Elementary School in Pekalongan City. The informants of this study were six educators and six parents. The data were obtained using interviews, observation, and documentation. The study results showed that using a communication platform, namely WhatsApp, could function as a learning medium at the elementary school level. Teachers did not use Learning Management systems (LMS) such as Google Classroom because it was not acceptable to parents and students found it difficult to operate in online learning. The results of this study have contributed to the lack of literature discussing the weaknesses of LMS and learning applications for elementary school students.